2022
DOI: 10.1108/sasbe-09-2021-0154
|View full text |Cite
|
Sign up to set email alerts
|

Assessing annual thermal comfort extent in central courtyards: Baghdad as a case study

Abstract: PurposeTraditional central courtyards have been advocated for being thermally efficient for hot-climate regions. However, exploring previous literature shows that it is not clear to what extent courtyards are truly thermally comfortable. This study determines the level of thermal comfort in residential courtyards in hot-climate regions, taking Baghdad as a case study.Design/methodology/approachThis study develops a novel Courtyard Thermal Usability Index (CTUI) to quantify the ability of courtyards to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Lizana, Lopez-Cabeza [20] found that the microclimate of the courtyard can greatly reduce the impact of urban overheating in the building, eliminating more than 88% of the uncomfortable time indoors. In Iraq, courtyards have been shown to provide occupants up to 38% more comfort throughout the year [21]. In short, the traditional open courtyard is believed to have a positive effect on reducing energy consumption and carbon emissions of the building [22][23][24].…”
Section: Literature Review 21 Traditional Courtyard Model and Its Ene...mentioning
confidence: 99%
“…Lizana, Lopez-Cabeza [20] found that the microclimate of the courtyard can greatly reduce the impact of urban overheating in the building, eliminating more than 88% of the uncomfortable time indoors. In Iraq, courtyards have been shown to provide occupants up to 38% more comfort throughout the year [21]. In short, the traditional open courtyard is believed to have a positive effect on reducing energy consumption and carbon emissions of the building [22][23][24].…”
Section: Literature Review 21 Traditional Courtyard Model and Its Ene...mentioning
confidence: 99%
“…Analyzing 360 courtyards with Envi-met 4.2, the study found that courtyards in Iraq offer only 38% comfortable hours annually. Key factors affecting thermal comfort include the courtyard's widthto-height ratio and the Mean Radiant Temperature (MRT), providing insights for designing efficient courtyards in hot climates [25].…”
Section: Introductionmentioning
confidence: 99%
“…A study has been conducted in Baghdad, Iraq, about the influence of the courtyard on the thermal comfort of the occupants. According to the findings, out of the total number of possible occupation hours in houses in Iraq each year, courtyards can provide up to 38% of comfortable hours [13]. Moreover, according to Radha [14], reaching better thermal comfort in the residential buildings in Sulaymaniyah, Northern Iraq, requires a hybrid ventilation system (passive and active) in the summer, especially during the months of July and August.…”
Section: Introductionmentioning
confidence: 99%